Effect of adding azithromycin to the antimalarials used for seasonal malaria chemoprevention on the nutritional status of African children. Issue 6 (16th April 2020) - Gore‐Langton, Georgia R.; Cairns, Matthew; Compaoré, Yves Daniel; Sagara, Issaka; Kuepfer, Irene; Zongo, Issaka; de Wit, Mariken M.; Barry, Amadou; Diarra, Modibo; Tapily, Amadou; Coumare, Samba; Thera, Ismail; et al.
Abstract: Objectives: Mass administration of azithromycin has reduced mortality in children in sub‐Saharan Africa but its mode of action is not well characterised. A recent trial found that azithromycin given alongside seasonal malaria chemoprevention was not associated with a reduction in mortality or hospital admissions in young children. We investigated the effect of azithromycin on the nutritional status of children enrolled in this study. Methods: A total of 19 578 children in Burkina Faso and Mali were randomised to receive either azithromycin or placebo alongside seasonal malaria chemoprevention with sulfadoxine–pyrimethamine plus amodiaquine monthly for three malaria transmission seasons (2014–2016). After each transmission season, anthropometric measurements were collected from approximately 4000 randomly selected children (2000 per country) at a cross‐sectional survey and used to derive nutritional status indicators. Binary and continuous outcomes between treatment arms were compared by Poisson and linear regression. Results: Nutritional status among children was poor in both countries with evidence of acute and chronic malnutrition (24.9–33.3% stunted, 15.8–32.0% underweight, 7.2–26.4% wasted). There was a suggestion of improvement in nutritional status in Burkina Faso and deterioration in Mali over the study period. At the end of each malaria transmission season, nutritional status of children did not differ between treatment arms (seasonal malaria chemoprevention plus azithromycin or placebo) in either the intention‐to‐treat or per‐protocol analyses (only children with at least three cycles of SMC in the current intervention year). Conclusions: The addition of azithromycin to seasonal malaria chemoprevention did not result in an improvement of nutritional outcomes in children in Burkina Faso and Mali. Abstract : Objectifs: L'administration massive d'azithromycine a réduit la mortalité infantile en Afrique subsaharienne mais son mode d'action n'est pas bien caractérisé. Un essai récent a révélé que l'azithromycine administrée parallèlement à la chimioprévention du paludisme saisonnier n'était pas associée à une réduction de la mortalité ou des hospitalisations chez les jeunes enfants. Nous avons étudié l'effet de l'azithromycine sur l'état nutritionnel des enfants inscrits à cette étude. Méthodes: 19.578 enfants au Burkina Faso et au Mali ont été randomisés pour recevoir soit de l'azithromycine soit un placebo parallèlement à une chimioprévention du paludisme saisonnier avec du sulfadoxine‐pyriméthamine plus de l'amodiaquine par mois pendant trois saisons de transmission du paludisme (2014‐2016). Après chaque saison de transmission, des mesures anthropométriques ont été recueillies auprès d'environ 4.000 enfants sélectionnés au hasard (2.000 par pays) lors d'une enquête transversale et utilisées pour dériver des indicateurs de l'état nutritionnel. Les résultats binaires et continus entre les bras de traitement ont été comparés par la régression linéaire et de Poisson. Résultats: L'état nutritionnel des enfants était médiocre dans les deux pays avec des signes de malnutrition aiguë et chronique (24, 9 à 33, 3% de retard de croissance, 15, 8 à 32, 0% d'insuffisance pondérale, 7, 2 à 26, 4% d'émaciation). Il a été suggéré une amélioration de l'état nutritionnel au Burkina Faso et une détérioration au Mali au cours de la période d'étude. A la fin de chaque saison de transmission du paludisme, l'état nutritionnel des enfants ne différait pas entre les bras de traitement (chimioprévention contre le paludisme saisonnier plus azithromycine ou placebo) dans les analyses en intention de traiter ou selon le protocole (seulement les enfants avec au moins trois cycles de chimioprévention dans l'année d'intervention en cours). Conclusions: L'ajout d'azithromycine à la chimioprévention du paludisme saisonnier n'a pas entraîné d'amélioration des résultats nutritionnels chez les enfants au Burkina Faso et au Mali.